Satellite DNA and related diseases - Rich, J.; Ogryzko, V.V.; Pirozhkova, I.V. (Вiopolymers and Cell, 2014)
Satellite DNA, also known as tandemly repeated DNA, consists of clusters of repeated sequences and represents a diverse class of highly repetitive elements. Satellite DNA can be divided into several classes according to the size of an individual repeat: microsatellites, minisatellites, midisatellites, and macrosatellites. Originally considered as «junk» DNA, satellite DNA has more recently been reconsidered as having various functions. Moreover, due to the repetitive nature of the composing elements, their presence in the genome is associated with high frequency mutations, epigenetic changes and modifications in gene expression patterns, with a potential to lead to human disease. Therefore, the satellite DNA study will be beneficial for developing a treatment of satellite-related diseases, such as FSHD, neurological, developmental disorders and cancers.